Evaluasi Materi Qira’ah Buku Ajar Bahasa Arab Pendekatan Saintifik Kurikulum 2013 - Shofiyatul Millah (CENDEKIA, 2021)
Abstract Evaluation is an assessment. The purpose of this paper is to discuss the evaluation of textbooks. The component that is evaluated is maharah qira'ah in the Arabic language teaching bookscientific approach 2013 curriculum grade IX Madrasah Tsanawiyah published by the Ministry of Religion of the Republic of Indonesia. The research used in this paper is descriptive analysis method. Data collection techniques use observation and documentation. The results obtained from this study are the material for al qira'ah Arabic books for class IX at the Madrasah Tsanawiyah level. The 2013 curriculum with a scientific approach published by the Ministry of Religion of the Republic of Indonesia in accordance with the standardization of core competency content of the 2013 curriculum. The results of the research will be presented as follows: The first chapter touches more on the spiritual realm (KI 1) and knowledge (KI 3), in the second chapter it touches the realm of knowledge (KI 3), in the third chapter there are many readings that discuss the realm of knowledge (KI 3) and the realm of attitude (KI 2), in the fourth chapter according to the spiritual realm (KI 1), attitude (KI 2), and knowledge (KI 3) , in the fifth chapter discusses attitudes (KI 2), skills (KI 4) and spirituality (KI 1) . When the contents of qira'ah in this book is related to the problem of skills, it has not been fully fulfilled because this book is consumed by children at the Madrasah Tsanawiyah or Junior High School level, which incidentally must be honed in their skills in the field of skills. Keywords: Evaluation; Alqira'a h Material; Textbooks.